Pengaruh Terpaan Konten Akun Instagram @ussfeeds terhadap Minat Baca di Kalangan Generasi Z - Latuputty, Jennifer Brigita; Gelgel, Ni Made Ras Amanda; Pradipta, Ade Devia; Cahyani, Dewi Yuri (E-Jurnal Medium, 2024)
According to a survey conducted by the OECD in 2019 regarding the reading interest of generation Z in Indonesia 62 out of 70 countries. The emergence of this fact, accompanied by the development of today's technology, has encouraged many transitions in the existence of media that initially moved conventionally to digital in order to be able to reach a wider community in an unlimited manner. The analysis in this study is based on the S-O-R theory (Stimulus, Organism, Responsive), using explanatory quantitative methods with a sample size of 122 respondents. The results of this study state that the influence between @ussfeeds Instagram account content on reading interest among generation Z are strong, unidirectional, and in moderate level of relationship. These results show that the quality of content produced by digital media such as @ussfeeds is impacting the increase of reading interest, especially among generation Z.